RISK FACTORS ASSOCIATED WITH THE BIRTH OF CHILDREN WITH A BODY WEIGHT LESS THAN 2500 G: RESULTS OF A RETROSPECTIVE COHORT MULTICENTER STUDY - I. A. Deev; K. V. Kulikova; O. S. Kobyakova; E. S. Kulikov; A. V. Holopov; N. A. Stepanov; I. N. Antonova; E. G. Bybchenko; K. E. Holtzman; E. N. Dorovskaya; E. N. Kozhevnikova; L. V. Ledyaykina; et al. (Педиатрическая фармакология, 2017)
Background. Improving nursing methods of newborns with birth weight less than 2500 g resulted in an increase in the proportion of children at risk for the development of severe disabling conditions. Objective: Our aim was to investigate the risk factors of the mother, associated with the birth of a child with a birth weight less than 2500 g. Methods. In a retrospective cohort study included 572 children born to 566 mothers in 5 perinatal centers. Risk assessment was carried out taking into account birth weight (in groups of children with normal, low, very low and extremely low birth weight). Results. Sample of mothers (n = 489), whose children had birth weight     2500 g, characterized by a mean age of 31 (26; 35) years, the growth of 164 (159; 168) cm, weighing when registering for pregnancy 62 (53; 74) and 70 kg (60; 80) kg just before birth. Among the independent predictors of birth weight infants were allocated as follows: maternal education (higher/more), mother occupation (housewife/other), presence of chronic diseases, anemia during pregnancy, the threat of premature births, growth and weight of the mother’s body before birth, weight gain body during pregnancy, body mass index (BMI) when registering for antenatal care in pregnancy and before delivery. Conclusion. Identified risk factors for maternal birth weight infants, which can be used to stratify pregnant women at risk.